Avalia????o da percep????o e das atitudes ambientais de estudantes de Institui????es de Ensino Superior (IES) p??blicas e privadas do estado de S??o Paulo - Tzortzis, Patricia Stor??poli (2017)
Higher Education Institutions are environments that, in addition to promoting and disseminating knowledge, have the possibility of applying and developing practices that generate improvements in the actions and attitudes of individuals. Higher Education Institutions play a fundamental role in sustainability, since their activities, including research, teaching and social engagement are of the utmost importance for the learning of an entire society. In order for an educational organization works on a daily basis, a number of requirements are needed such as: water use, use of electricity, sewage treatment, garbage collection, and appropriate waste disposal (laboratories). In this sense, the Institution of Higher Education has an important contribution in what concerns the promotion of sustainable practices and actions to embed in the culture of the individual notions and knowledge about the environment, so that it can act and provide improvements for its and the next Generations. Critical environmental education has the power to provoke perceptions and reflections in the individual according to the environment in which it is inserted. In this way, this individual can have conditions and capacity and evaluate and identify environmental problems, and present actions, proposals and environmental solutions, generating significant contributions to the planet and living beings. In this context, the present study aims to evaluate the perception and environmental attitudes of undergraduate students of the Business Administration course of public and private higher education institutions of the state of S??o Paulo. For this purpose, a quantitative descriptive research will be carried out involving first and last year students of the Business Administration course of two Public Higher Education Institutions and two Private Higher Education Institutions of the state of S??o Paulo. By the fact that executives and administrators are professionals that aim at a business solution, that work in non-governmental organizations, public and private and for still daily dealing with topics such as: planning, organization, financial, physical, human and technological resources, it is important that This type of professional has adequate knowledge to deal with environmental issues, focusing on the sustainability tripod, providing benefits to society and the environment. The results of the research showed that the undergraduate courses in Administration studied have few subjects that deal with subjects related to sustainability in the curricular matrix and that this is treated in a transdisciplinary way in the course. The analysis of variance indicated that there is a significant difference in the student perception about the sustainability of the Higher Education Institution in which they study. However, it did not matter the type of institution - public or private - as the formation of the perception of sustainability in the evaluation of the students. Again, the typification of the Institution of Higher Education was not decisive on the dependent variables. That is, the Institution of Higher Education is public or private, apparently, does not influence the orientation of the environmental attitude declared by university students. Apparently, the greater permanence in the course did not influence the attitude and the environmental conscience of the students. In the same way, as early as the early years, students have the same perception of veterans as the sustainability of the institution.